New Developed DR Detector Performs Radiographs of Hand, Pelvic and Premature Chest Anatomies at a Lower Radiation Dose and/or a Higher Image Quality. - Precht, Helle; Tingberg, Anders; Waaler, Dag; Outzen, Claus (Journal of Digital Imaging, 2014)
A newly developed Digital Radiography (DR) detector has smaller pixel size and higher fill factor than earlier detector models. These technical advantages should theoretically lead to higher sensitivity and higher spatial resolution, thus making dose reduction possible without scarifying image quality compared to previous DR detector versions. To examine whether the newly developed Canon CXDI-70C DR detector provides an improved image quality and/or allows for dose reductions in hand and pelvic bone examinations as well as premature chest examinations, compared to the previous (CXDI-55C) DR detector version. A total of 450 images of a technical Contrast-Detail phantom were imaged on a DR system employing various kVp and mAs settings, providing an objective image quality assessment. In addition, 450 images of anthropomorphic phantoms were taken and analyzed by three specialized radiologists using Visual Grading Analysis (VGA). The results from the technical phantom studies showed that the image quality expressed as IQF values was on average approximately 45 % higher with the CXDI-70C detector compared to the CXDI-55C detector. Consistently, the VGA results from the anatomical phantom studies indicated that by using the CXDI-70C detector, diagnostic image quality could be maintained at a dose reduction of in average 30 %, depending on anatomy and kVp level. This indicates that the CXDI-70C detector is significantly more sensitive than the previous model, and supports a better clinical image quality. By using the newly developed DR detector a significant dose reduction is possible while maintaining image quality.